Copanlisib for the treatment of adults with relapsed follicular lymphoma. Issue 8 (2nd August 2020) - Magagnoli, Massimo; Carlo-Stella, Carmelo; Santoro, Armando
ABSTRACT: Introduction: Follicular lymphoma (FL) is the second most common histotype of lymphoma and is considered an incurable disease. The need for new treatment options has led to the development of innovative targeted agents, including inhibitors of the phosphatidylinositol-3-kinase (PI3K) pathway. Areas covered: Copanlisib, an intravenous pan–class I PI3K inhibitor, has been approved by the US Food and Drug Administration (FDA) for the treatment of relapsed FL in patients who have received at least two prior systemic therapies. In this article, we critically review the mechanism of action, clinical efficacy, safety, dosage, administration, and role of copanlisib in the treatment of relapsed FL. Expert opinion: Treatment with copanlisib results in clinically relevant and durable responses in heavily pretreated patients with relapsed or refractory FL. In addition, copanlisib has a manageable safety profile in this population, with low rates of severe hepatic transaminitis, diarrhea, colitis, and noninfectious pneumonitis. Further investigations of copanlisib within combination regimens will potentially allow to move copanlisib to an earlier line of therapy for FL. However, results of the CHRONOS-4 clinical trial evaluating copanlisib with standard chemoimmunotherapy (rituximab with bendamustine or CHOP) are not yet available.